Effect of mycorrhizae on peanut cultivation in a grayish-brown ochric soil - González Ramírez, Gladia (2022)
The effect of mycorrhizal strains on the effectiveness of symbiosis and productivity of peanut (Arachis hypogaea L.) cultivar ‘Cascajal rosado’ was evaluated, two experiments were established from June-December 2016; one in the acclimatization phase in the Faculty of Technical and Agricultural Sciences and the other in the “Mahanain” Farm of the CCS ‘José Santiago Ercilla’, in a grayish brown ochre soil in the northern zone of the municipality of Las Tunas. The treatments used were: control, NPK application and the use of four mycorrhizal strains (Rhizophagus intraradices, Funneliformis mosseae, Glomus cubense and Claroideoglomus claroideum). The following were determined: root length, plant height, number of pods-plant-1, biomass of 100 grains, mycorrhizal and oil percentage and oil acidity index. Agricultural yield was calculated. Data were subjected to analysis of variance and comparison of means. The applications of mycorrhizal strains caused a positive response in peanut yields. The best performing strain in most of the variables studied was R. intraradices followed by G. cubense and F. mosseae. The highest gains and the lowest costs per biomass gain were obtained with the use of R. intraradices.